LEGAL ANALYSIS OF THE ONLINE VISA SYSTEM FOR FOREIGNERS ENTERING INDONESIA - Muhammad Fadhil Thalib; Laily Washliati; Ramon Nofrial (CV. RADJA PUBLIKA, 2025)
Digital transformation in public services is a strategic step towards achieving effective, efficient, and accountable services. One manifestation of this transformation is the implementation of an online visa system by the Directorate General of Immigration as part of immigration service reform. This research is motivated by the importance of legal certainty and the effectiveness of the online visa system for foreigners wishing to enter Indonesia, considering that this system concerns the legal and administrative rights of foreign citizens, as well as the credibility of Indonesian public services at the global level. This research aims to analyze laws and regulations, assess the effectiveness of the online visa system implementation, and identify obstacles and efforts to overcome them in order to strengthen legal certainty and service efficiency. The method used is a legal research method with a normative and empirical legal approach, using secondary data in the form of laws and regulations, official documents, and primary data in the form of interviews with immigration officials and visa applicants in Batam City. The results show that the legal framework of the online visa system is structured hierarchically, but there are still inconsistencies between the substance of the regulations and their implementation in practice. This system has improved process efficiency, but is not yet fully effective due to technical challenges, disparities in understanding among officials, and low digital literacy among some applicants. Mitigation efforts have been implemented through digital innovation and strengthened regulations, but further integration of the structure, substance, and culture of fairness in the legal system is still needed. The study recommends that the government and relevant agencies improve staff training, simplify technical procedures, expand reach, and ensure equal access for all service users to achieve an effective online visa system based on legal certainty.